Wildlife consumption is widespread across Equatorial Guinea and hunted species are more threatened now than 35 years ago - José L. Tella; Iñigo Palacios-Martínez; Pedro Romero-Vidal; Guillermo Blanco; Javier Juste (Biological Conservation, 2026)

Changes in community composition and functional diversity of European bats under climate change - Penelope C. Fialas; Luca Santini; Danilo Russo; Francisco Amorim; Hugo Rebelo; Roberto Novella‐Fernandez; Francisco Marques; Adi Domer; Adriana Vella; Adriano Martinoli; Aleksandra Figurek; Asaf Tsoar; et al. (Conservation Biology, 2025)
Climate change is predicted to drive geographical range shifts that will result in changes in species diversity and functional composition and have potential repercussions for ecosystem functioning. However, the effect of these changes on species composition and functional diversity (FD) remains unclear, especially for mammals, specifically bats. We used species distribution models and a comprehensive ecological and morphometrical trait database to estimate how projected future climate and land‐use changes could influence the distribution, composition, and FD of the European bat community. Future bat assemblages were predicted to undergo substantial shifts in geographic range and trait structure. Range suitability decreased substantially in southern Europe and increased in northern latitudes. Our findings highlight the potential for climate change to drive shifts in bat FD, which has implications for ecosystem function and resilience at a continental scale. It is important to incorporate FD in conservation strategies. These efforts should target species with key functional traits predicted to be lost and areas expected to experience losses in FD. Conservation strategies should include habitat and roost protection, enhancing landscape connectivity, and international monitoring to preserve bat populations and their ecosystem services.

A global initiative for ecological and evolutionary hologenomics - Aoife Leonard; Javier Abalos; Titus Adhola; Windsor Aguirre; Ostaizka Aizpurua; Shahzad Ali; Franco Andreone; Fabien Aubret; Hefer D. Ávila-Palma; Lizbeth Fabiola Bautista Alcantara; Juan F. Beltrán; Rachel Berg; et al. (Trends in Ecology & Evolution, 2024)

Expert range maps of global mammal distributions harmonised to three taxonomic authorities - Charles J. Marsh; Yanina V. Sica; Connor J. Burgin; Wendy A. Dorman; Robert C. Anderson; Isabel del Toro Mijares; Jessica G. Vigneron; Vijay Barve; Victoria L. Dombrowik; Michelle Duong; Robert Guralnick; Julie A. Hart; et al. (Journal of Biogeography, 2022)
Aim Comprehensive, global information on species' occurrences is an essential biodiversity variable and central to a range of applications in ecology, evolution, biogeography and conservation. Expert range maps often represent a species' only available distributional information and play an increasing role in conservation assessments and macroecology. We provide global range maps for the native ranges of all extant mammal species harmonised to the taxonomy of the Mammal Diversity Database (MDD) mobilised from two sources, the Handbook of the Mammals of the World (HMW) and the Illustrated Checklist of the Mammals of the World (CMW). Location Global. Taxon All extant mammal species. Methods Range maps were digitally interpreted, georeferenced, error‐checked and subsequently taxonomically aligned between the HMW (6253 species), the CMW (6431 species) and the MDD taxonomies (6362 species). Results Range maps can be evaluated and visualised in an online map browser at Map of Life ( mol.org ) and accessed for individual or batch download for non‐commercial use. Main conclusion Expert maps of species' global distributions are limited in their spatial detail and temporal specificity, but form a useful basis for broad‐scale characterizations and model‐based integration with other data. We provide georeferenced range maps for the native ranges of all extant mammal species as shapefiles, with species‐level metadata and source information packaged together in geodatabase format. Across the three taxonomic sources our maps entail, there are 1784 taxonomic name differences compared to the maps currently available on the IUCN Red List website. The expert maps provided here are harmonised to the MDD taxonomic authority and linked to a community of online tools that will enable transparent future updates and version control.

Pan African phylogeography and palaeodistribution of rousettine fruit bats: Ecogeographic correlation with Pleistocene climate vegetation cycles - Tereza Stribna; Dušan Romportl; Jan Demjanovič; Anna Vogeler; Marco Tschapka; Petr Benda; Ivan Horáček; Javier Juste; Steven M. Goodman; Pavel Hulva (Journal of Biogeography, 2019)
Aim The impact of Pleistocene climatic oscillations on tropical biomes is associated with changes in the extent of forest cover. Fruit bats have played a role in woodland dynamics via pollination and seed dispersal. We hypothesized that phylogeographic patterns of Rousettus on continental Africa and adjacent islands should show a signature of pluvial‐drought cycles, involving demographic expansions and contractions. Location Afrotropical, Malagasy and Saharo‐Arabian biogeographic realms. Taxon Genus Rousettus (Pteropodidae). Methods Phylogeographic and population genetic approaches using mitochondrial and microsatellite data were integrated with species distribution modelling of currently suitable habitats and those of the Last Glacial Maximum using climate simulations. Results Phylogenetic reconstruction yielded an Asian outgroup followed by pectinate branching of the Indian Ocean taxa and Rousettus aegyptiacus . While nuclear microsatellites were homogeneous across the African mainland, two mitochondrial haplogroups were found. Haplogroup I is widespread in regions with extensive tree cover, including tropical rain forests, and has close relationships to isolated lineages in the Middle East and islands in the Gulf of Guinea. Haplogroup II is sister to the rest of the R. aegyptiacus radiation and is found in eastern and southern Africa and the Sudanian savanna in habitats with semi‐open land cover. Main Conclusion Palaeodistributional modelling ascertained that the Indian Ocean islands provided more extensive areas of suitable habitat in the past relative to conditions today, suggesting stepping stone connectivity between Asia and Africa during Pleistocene interpluvial sea‐level lowstands. Inverse pluvial‐drought demography was detected in lineages ancestral to recent haplogroups, providing evidence of past forest refugia and complex ecogeographic scenarios of haplogroup origins involving allopatry and parapatry connected with the eastern Afromontane biodiversity hotspot, and subsequent admixture of nuclear gene pools. The Middle Eastern lineage probably originated during pluvial green Sahara periods, possibly in co‐evolution with ancestors of tree crop species domesticated later during the Neolithic revolution. The keystone role of rousettine bats for forest regeneration and their ability to pioneer dry and distant habitats emphasize their role in conservation biology and restoration ecology.

Unavailable names in the Myotis nattereri species complex - Manuel Ruedi; Sébastien J. Puechmaille; Carlos Ibáñez; Javier Juste (Journal of Biogeography, 2019)
The discovery of new species of mammals in Europe is a rare event, but owing to recent progress in genetic methods used to survey current biodiversity, such discoveries have been accumulating during the last decades. The naming of these new taxa has important bearings in conservation, as this is the first step needed for them to be recognised by the scientific community but also legally. The naming of new animal species, however, needs to follow the strict rules of the International Code of Zoological Nomenclature in order to be available and to provide a stable basis for further taxonomic research. We report here a case where new names have been improperly proposed to designate distinctive lineages in the Natterer's bat species complex. As these new names do not follow several mandatory rules imposed by the Code, they are declared unavailable and are not to be used for further taxonomy studies.

Ignoring seasonal changes in the ecological niche of non-migratory species may lead to biases in potential distribution models: lessons from bats - Sonia Smeraldo; Mirko Di Febbraro; Luciano Bosso; Carles Flaquer; David Guixé; Fulgencio Lisón; Angelika Meschede; Javier Juste; Julia Prüger; Xavier Puig-Montserrat; Danilo Russo (Biodiversity and Conservation, 2018)

Concealed by darkness: interactions between predatory bats and nocturnally migrating songbirds illuminated by DNA sequencing - Carlos Ibáñez; Ana G. Popa‐Lisseanu; David Pastor‐Beviá; Juan L. García‐Mudarra; Javier Juste (Molecular Ecology, 2016)
Recently, several species of aerial‐hawking bats have been found to prey on migrating songbirds, but details on this behaviour and its relevance for bird migration are still unclear. We sequenced avian DNA in feather‐containing scats of the bird‐feeding bat Nyctalus lasiopterus from Spain collected during bird migration seasons. We found very high prey diversity, with 31 bird species from eight families of Passeriformes, almost all of which were nocturnally flying sub‐Saharan migrants. Moreover, species using tree hollows or nest boxes in the study area during migration periods were not present in the bats’ diet, indicating that birds are solely captured on the wing during night‐time passage. Additional to a generalist feeding strategy, we found that bats selected medium‐sized bird species, thereby assumingly optimizing their energetic cost‐benefit balance and injury risk. Surprisingly, bats preyed upon birds half their own body mass. This shows that the 5% prey to predator body mass ratio traditionally assumed for aerial hunting bats does not apply to this hunting strategy or even underestimates these animals’ behavioural and mechanical abilities. Considering the bats’ generalist feeding strategy and their large prey size range, we suggest that nocturnal bat predation may have influenced the evolution of bird migration strategies and behaviour.

Unravelling the evolutionary history and future prospects of endemic species restricted to former glacial refugia - Orly Razgour; Irene Salicini; Carlos Ibáñez; Ettore Randi; Javier Juste (Molecular Ecology, 2015)
The contemporary distribution and genetic composition of biodiversity bear a signature of species’ evolutionary histories and the effects of past climatic oscillations. For many European species, the Mediterranean peninsulas of Iberia, Italy and the Balkans acted as glacial refugia and the source of range recolonization, and as a result, they contain disproportionately high levels of diversity. As these areas are particularly threatened by future climate change, it is important to understand how past climatic changes affected their biodiversity. We use an integrated approach, combining markers with different evolutionary rates and combining phylogenetic analysis with approximate Bayesian computation and species distribution modelling across temporal scales. We relate phylogeographic processes to patterns of genetic variation in Myotis escalerai , a bat species endemic to the Iberian Peninsula. We found a distinct population structure at the mitochondrial level with a strong geographic signature, indicating lineage divergence into separate glacial refugia within the Iberian refugium. However, microsatellite markers suggest higher levels of gene flow resulting in more limited structure at recent time frames. The evolutionary history of M. escalerai was shaped by the effects of climatic oscillations and changes in forest cover and composition, while its future is threatened by climatically induced range contractions and the role of ecological barriers due to competition interactions in restricting its distribution. This study warns that Mediterranean peninsulas, which provided refuge for European biodiversity during past glaciation events, may become a trap for limited dispersal and ecologically limited endemic species under future climate change, resulting in loss of entire lineages.

The shaping of genetic variation in edge‐of‐range populations under past and future climate change - Orly Razgour; Javier Juste; Carlos Ibáñez; Andreas Kiefer; Hugo Rebelo; Sébastien J. Puechmaille; Raphael Arlettaz; Terry Burke; Deborah A. Dawson; Mark Beaumont; Gareth Jones (Ecology Letters, 2013)
With rates of climate change exceeding the rate at which many species are able to shift their range or adapt, it is important to understand how future changes are likely to affect biodiversity at all levels of organisation. Understanding past responses and extent of niche conservatism in climatic tolerance can help predict future consequences. We use an integrated approach to determine the genetic consequences of past and future climate changes on a bat species, Plecotus austriacus . Glacial refugia predicted by palaeo‐modelling match those identified from analyses of extant genetic diversity and model‐based inference of demographic history. Former refugial populations currently contain disproportionately high genetic diversity, but niche conservatism, shifts in suitable areas and barriers to migration mean that these hotspots of genetic diversity are under threat from future climate change. Evidence of population decline despite recent northward migration highlights the need to conserve leading‐edge populations for spearheading future range shifts.

Phylogeny and systematics of O ld W orld serotine bats (genus E ptesicus , V espertilionidae, C hiroptera): an integrative approach - Javier Juste; Petr Benda; Juan Luis Garcia‐Mudarra; Carlos Ibáñez (Zoologica Scripta, 2013)
Integrative taxonomy aims to document biodiversity by incorporating all useful characters to increase confidence in hypotheses about phylogenetic relationships. In this study, we combine data obtained independently from morphology, two maternally inherited mt DNA genes and two biparentally inherited nu DNA genes to make phylogenetic and taxonomic hypotheses about the Palaearctic members of the bat genus E ptesicus ( V espertilionidae). This genus is distributed worldwide (except for A ntarctica) and is highly diversified, presenting one of the most entangled taxonomic puzzles among all mammals. Our results support restoring the genus R hyneptesicus and separating E . isabellinus and E . pachyomus from E . serotinus and E . ognevi and E . anatolicus from E . bottae . Differences in the phylogenetic hypotheses from mt DNA and nu DNA data suggest the occurrence within E . serotinus of evolutionary processes such as mt DNA capture and secondary contacts between partially differentiated ecomorphs. These two evolutionary processes deserve more in‐depth studies within the group.

Phylogeography and postglacial recolonization of Europe by Rhinolophus hipposideros : evidence from multiple genetic markers - Serena E. Dool; Sébastien J. Puechmaille; Christian Dietz; Javier Juste; Carlos Ibáñez; Pavel Hulva; Stéphane G. Roué; Eric J. Petit; Gareth Jones; Danilo Russo; Roberto Toffoli; Andrea Viglino; et al. (Molecular Ecology, 2013)
The demographic history of Rhinolophus hipposideros (lesser horseshoe bat) was reconstructed across its European, North African and Middle‐Eastern distribution prior to, during and following the most recent glaciations by generating and analysing a multimarker data set. This data set consisted of an X‐linked nuclear intron (Bgn; 543 bp), mitochondrial DNA (cytb‐ tRNA ‐control region; 1630 bp) and eight variable microsatellite loci for up to 373 individuals from 86 localities. Using this data set of diverse markers, it was possible to determine the species’ demography at three temporal stages. Nuclear intron data revealed early colonization into Europe from the east, which pre‐dates the Quaternary glaciations. The mtDNA data supported multiple glacial refugia across the Mediterranean, the largest of which were found in the Ibero‐Maghreb region and an eastern location (Anatolia/Middle East)–that were used by R. hipposideros during the most recent glacial cycles. Finally, microsatellites provided the most recent information on these species’ movements since the Last Glacial Maximum and suggested that lineages that had diverged into glacial refugia, such as in the Ibero‐Maghreb region, have remained isolated. These findings should be used to inform future conservation management strategies for R. hipposideros and show the power of using a multimarker data set for phylogeographic studies.

Deep differentiation between and within Mediterranean glacial refugia in a flying mammal, the Myotis nattereri bat complex - Irene Salicini; Carlos Ibáñez; Javier Juste (Journal of Biogeography, 2013)
Aim The role of glacial refugia in the biogeographical patterns in the Western Palaearctic region has been widely discussed, but many questions remain unresolved. We examined the biogeography, genetic diversity, spatial distribution and evolutionary history of the Myotis nattereri bat species complex to investigate the presence of multiple refugia and the persistence of Quaternary differentiation between and within Mediterranean refugia in a flying mammal. Location Western Palaearctic region (central and southern Europe and north‐western Maghreb). Methods We analysed three mitochondrial fragments (cytochrome b , NADH dehydrogenase subunit 1 and the control region; 1570 bp) from 136 individuals of the M. nattereri complex sampled from 87 different localities using a range of phylogenetic techniques. Divergences among clades were also dated using a Bayesian coalescence approach. Results Phylogenetic analyses identified four main lineages, coincident with the four cryptic species recently described. Each species is further subdivided into well‐supported lineages with evident geographical structure. Estimates of genetic diversity and polymorphism were very high for the majority of subclades, with the exception of M. nattereri s.s. Main conclusions The M. nattereri bat complex comprises four species whose distributions in the Western Palaearctic correspond to four main glacial refugia (Iberia, Italy, Balkans and Morocco). These species are the result of long‐term isolation (remarkable in a flying mammal) over several glacial cycles. The Balkan species expanded into central Europe in a rapid recolonization process. Both the Iberian and Italian peninsulas show a clear pattern of refugia‐within‐refugia in their genetic structuring, with a deeply differentiated southern Italian clade. Morocco shows two markedly differentiated lineages, probably separated by the Atlas Mountains. The legacy of Pleistocene cycles is evident in both the speciation and the intraspecific diversification events.

Detection of alpha and betacoronaviruses in multiple Iberian bat species - Ana Falcón; Sonia Vázquez-Morón; Inmaculada Casas; Carolina Aznar; Guillermo Ruiz; Francisco Pozo; Pilar Perez-Breña; Javier Juste; Carlos Ibáñez; Inazio Garin; Joxerra Aihartza; Juan E. Echevarría (Archives of Virology, 2011)

Assessing survival in a multi-population system: a case study on bat populations - Eleni Papadatou; Carlos Ibáñez; Roger Pradel; Javier Juste; Olivier Gimenez (Oecologia, 2011)

Two sibling species sympatrically breeding: a new conservation concern for the critically endangered Balearic shearwater - Meritxell Genovart; Javier Juste; Daniel Oro (Conservation Genetics, 2006)

Diversity and status of sea turtle species in the Gulf of Guinea islands - Javier Castroviejo; Javier Juste B; Jaime Del Val Pérez; Ramon Castelo; Ramon Gil (Biodiversity and Conservation, 1994)

Bats of the Gulf of Guinea islands: faunal composition and origins - Javier Juste B; Carlos Ibaez (Biodiversity and Conservation, 1994)

Biodiversity conservation in the Gulf of Guinea islands: taking stock and preparing action - B Javier Juste; John E. Fa (Biodiversity and Conservation, 1994)